Pandangan Masyarakat Kota Ambon Terhadap Penikahan Beda Agama Dalam Tinjauan Soisologi Hukum - Putuhena, Mohammad Sarfan Basyir (Al-Mizan (e-Journal), 2024)
This study aims to analyze the views of the Ambon city community towards interfaith marriage.This research uses empirical normative methods, both legislative and legal sociology approaches. The types of primary data sources obtained come from observations, and interviews as well as secondary data in the form of literature studies. Furthermore, data was collected and analyzed in a qualitative descriptive manner, the results of this study showed that, the public's perception and understanding of interfaith marriage all agreed that interfaith marriage is forbidden (haram) and automatically invalid, interfaith marriage is also one of the deviations that violate religious law and positive law in Indonesia.